Prevention and Treatment of Side Effects of Immunotherapy for Bladder Cancer - Lou, Kecheng; Feng, Shangzhi; Zhang, Guoxi; Zou, Junrong; Zou, Xiaofeng (Frontiers in Oncology, 2022)
Bladder cancer is one of the most important tumors of the genitourinary system, associated with high morbidity and mortality rates. Over the years, various antitumor treatments have been developed, and immunotherapy is one of the most effective methods. Immunotherapy aims to activate the body's immune system to kill cancer cells. It has been established that immunotherapy drugs can be classified into "non-targeted" and "targeted" drugs depending on their site of action. Immunotherapy is reportedly effective for bladder cancer. Even though it can attack cancer cells, it can also cause the immune system to attack healthy cells, which can occur at any time during treatment and sometimes even after immunotherapy is stopped. Importantly, different types of immunotherapies can cause different side effects. Side effects may manifest themselves as signs or as symptoms. The prevention and treatment of side effects caused by immunotherapy is an important part of cancer patient management.